FAKTOR-FAKTOR YANG MEMENGARUHI LITERASI KEUANGAN PADA MAHASISWA UNIVERSITAS WIDYA DHARMA KALTEN - ISTIKHOMAH TRISNA SARI; Oki Kuntaryanto; Susyanti (Widya Dharma Journal of Business - WIJoB, 2025)
This study aims to determine whether parental education level (X1), parental income (X2), student lifestyle (X3), social environment influence (X4), and financial education on college (X5) have an effect to students’ financial literacy (Y). Questionnaires were utilized as the primary tool for collecting data from 103 respondents, of which 71 were valid and usable. This research employs several data analysis methods, such as descriptive analysis, instrument evaluation (including validity and reliability tests), and classical assumption tests, namely normality, multicollinearity, and heteroscedasticity tests and statistical tests (t-test and F-test).The results of the study show that parental education level, parental income, student lifestyle, and financial education on college do not significantly effect to students' financial literacy. However, students' financial literacy is notably affected by their social environment. Keywords: Parental Education Level, Parental Income, Student Lifestyle, Social Environment Influence, Financial Education on Collage, Financial Literacy